Analysis of the Impact of Work Discipline and Social Security on Employee Work Productivity at PT. Sawitta Unggul Jaya - Muhamad Zakaria; Teguh Wahyono; Yohny Anwar (Jurnal Fokus Manajemen, 2026)
This study aims to analyze the effect of Work Discipline and Social Security on Employee Work Productivity at PT. Sawitta Unggul Jaya. This research uses a quantitative approach with a survey method. The data were collected through questionnaires distributed to employees and analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The data analysis techniques include the multicollinearity test, t-test (partial), F-test (simultaneous), and the coefficient of determination (R²). The results show that partially Work Discipline has a positive and significant effect on Employee Work Productivity, with a t-value of 4.182 and a significance level of 0.000. Social Security also has a positive and significant effect on Employee Work Productivity, with a t-value of 5.564 and a significance level of 0.000. Simultaneously, Work Discipline and Social Security have a significant effect on Employee Work Productivity, as indicated by an F-value of 83.261 and a significance level of 0.000. The coefficient of determination (R²) value of 0.649 indicates that 64.9% of the variation in Employee Work Productivity can be explained by Work Discipline and Social Security, while the remaining 35.1% is influenced by other variables not examined in this study. Based on these findings, it can be concluded that Work Discipline and Social Security are important factors that need to be considered by the company in an effort to improve Employee Work Productivity. Therefore, PT. Sawitta Unggul Jaya is advised to enhance the implementation of work discipline and provide adequate social security to support optimal employee productivity.